The Vietnam national seismological network: establishment and development - Van, Dinh Quoc; Anh, Nguyen Xuan; Binh, Nguyen Xuan; Minh, Le Huy; Giang, Nguyen Van; Minh, Nguyen Le; Hung, Nguyen Tien; Khoi, Le Quang; Thuy, Nguyen Ngoc; Son, Le Tu; Phung, Dinh Doan; Ngoan, Doan Thi; et al. (Vietnam Journal of Marine Science and Technology, 2017)
In this article, by combining/following previous publications, we summarize the history of nearly 100 years of development of the Vietnam seismological network and its achievements in earthquake monitoring and seismological research to contribute to prevention and mitigation of natural disasters and sustainable development of the country. Earthquake observation in Vietnam has gone through many stages of development, the first seismic station was established in Sapa by the French in 1924. In the years of  70-80s of the 20th Century, the earthquake monitoring network of Vietnam consisted of 7 stations, including five stations distributed in the Northern part (Phu Lien, Sa Pa, Bac Giang, Hoa Binh, Tuyen Quang) and two stations located in the south (Nha Trang and Da Lat). In the period from 1990 to 2005, the national seismological network with 24 digital seismographs and short-period sensors was created and distributed throughout the country. Today, earthquake monitoring in Vietnam has made great progress, the new seismological network with 30 broadband stations with advanced earthquake monitoring technology been established completely in 2017. The international cooperation on earthquake monitoring and seismological research is  always promoted and expanded, over the past 60 years, IGP has collaborated with many scientific organizations from different countries such as Russia, France, China, Japan, Poland, The United State of America,... and prestigious international organizations as UNDP, PTWC, CTBTO, IRIS, ADPC, RIMES,.. Through these cooperations, many research projects have been done and Vietnamese seismologists have been trained and educated at different levels that help to improve their knowledge earthquake monitoring and seismological research. Besides operating the national seismological network, some local seismic networks have also been established by Institute of Geophysics for many years to monitor and study induced seismicity in some reservoirs of hydropower dams such as Son La, Hoa Binh, Tri An, Yaly, Song Tranh, Lai Chau, Huoi Quang, Ban Chat,...